Preparation and characterization of an aromatic polyester/polyaniline composite and its improved counterpart - C. S. Wu (eXPRESS Polymer Letters)
Poly(butylene terephthalate) (PBT) composites containing polyaniline (PANI) were prepared using a melt-blending process. Maleic anhydride-grafted PBT (PBT-g-MA) and PANI were used to improve the compatibility of PANI within the PBT matrix. PBT-g-MA/PANI composites exhibited noticeably superior mechanical properties compared with those of PBT/PANI due to greater compatibility with the added PANI. The antibacterial and antistatic properties of the composites were also evaluated. Escherichia coli were chosen as the standard bacteria for determining the antibacterial properties of the composite materials. The PBT-g-MA/PANI composites showed markedly enhanced antibacterial and antistatic properties compared to PBT/PANI composites due to the formation of imide bonds from condensation of the anhydride carboxyl acid groups of PBT-g-MA with the amino groups of PANI. The optimal level of PANI in the composites was 9 wt%, as excess PANI led to separation of the two organic phases, lowering their compatibility.